Solar ultraviolet‐induced DNA damage response: Melanocytes story in transformation to environmental melanomagenesis. (8th May 2020) - Sarkar, Soumyadeep; Gaddameedhi, Shobhan
Abstract: Exposure to sunlight is both beneficial, as it heats the planet to a comfortable temperature, and potentially harmful, since sunlight contains ultraviolet radiation (UVR), which is deemed detrimental for living organisms. Earth's ozone layer plays a vital role in blocking most of the extremely dangerous UVC; however, low frequency/energy UVR (i.e., UVB and UVA) seeps through in minute amount and reaches the Earth's surface. Both UVB and UVA are physiologically responsible for a plethora of skin ailments, including skin cancers. The UVR is readily absorbed by the genomic DNA of skin cells, causing DNA bond distortion and UV‐induced DNA damage. As a defense mechanism, the DNA damage response (DDR) signaling in skin cells activates nucleotide excision repair (NER), which is responsible for the removal of UVR‐induced DNA photolesions and helps maintain the genomic integrity of the cells. Failure of proper NER function leads to mutagenesis and development of skin cancers. One of the deadliest form of skin cancers is melanoma which originates upon the genetic transformation of melanocytes, melanin producing skin cells. NER is a well‐studied DNA repair system in the whole skin, as a tissue, but not much is known about it in melanocytes. Therefore, this review encapsulates NER in melanocytes, with a specific focus on its functional regulators and their cross talks due to skin heterogeneity and divulging the potential knowledge gap in the field.